2016
DOI: 10.1038/srep36395
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of arrhythmogenesis related to calcium-driven alternans in a model of human atrial fibrillation

Abstract: The occurrence of atrial fibrillation (AF) is associated with progressive changes in the calcium handling system of atrial myocytes. Calcium cycling instability has been implicated as an underlying mechanism of electrical alternans observed in patients who experience AF. However, the extent to which calcium-induced alternation of electrical activity in the atria contributes to arrhythmogenesis is unknown. In this study, we investigated the effects of calcium-driven alternans (CDA) on arrhythmia susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…They concluded that decreased RyR2 inactivation is the only parameter variation that reproduces AF-associated APD alternans behavior at relatively slow rates and that RyR2 kinetics may play a critical role in governing proarrhythmic APD alternans. In a subsequent study with a 3-dimensional human atrial model, they noted a critical role of Ca 2+ -driven alternans, not only in the initiation of AF, but also in its persistence by causing unstable scroll waves that meander and break up to produce multiple daughter wavelets (24).…”
Section: Discussionmentioning
confidence: 98%
“…They concluded that decreased RyR2 inactivation is the only parameter variation that reproduces AF-associated APD alternans behavior at relatively slow rates and that RyR2 kinetics may play a critical role in governing proarrhythmic APD alternans. In a subsequent study with a 3-dimensional human atrial model, they noted a critical role of Ca 2+ -driven alternans, not only in the initiation of AF, but also in its persistence by causing unstable scroll waves that meander and break up to produce multiple daughter wavelets (24).…”
Section: Discussionmentioning
confidence: 98%
“…266 Overall, computer modeling clearly suggests that elevated Ca 2+ -driven APD alternans leads to increased arrhythmia vulnerability, complexity, and persistence due to increased heterogeneity of repolarization in atria. 267 …”
Section: Calcium-dependent Acquired Arrhythmiasmentioning
confidence: 99%
“…Models can be used to extrapolate changes observed in preclinical studies in Ca 2+ dynamics and Ca 2+ regulation into human contexts. Models have been successfully used to predict the effect of L-type Ca 2+ channel relocation in patients with heart failure with increased arrhythmogenic risk and to explain the role of a decrease in the function of sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase on action potential alternans in patients with atrial fibrillation (AF) or the role of Ca 2+ dysregulation in the increase in arrhythmia complexity and substrate 8183 . Analogously to genetic and drug studies, the characterization of physiological and pathological regulation of channels can be done in expression systems and interpreted within the context of human physiology 75 .…”
Section: Modelling Human Cardiac Cellsmentioning
confidence: 99%
“…Atrial computational models have made major contributions in understanding how intrinsic atrial structural and electrophysiological heterogeneities predispose to atrial arrhythmias 132135 . Examples of such contributions include investigating the role of pulmonary vein triggers in initiating paroxysmal AF, determining the mechanisms of lone paroxysmal AF that arise from inherited ion channel dysfunction, establishing the mechanisms for atrial alternans, elucidating the role of the ganglionic plexi in initiating AF and revealing the contribution of the electrical uncoupling between the endocardial and epicardial layers 83,136140 . In the past couple of years, the understanding of the role of fibrosis in maintaining persistent AF has led to a number of new computational studies aimed at determining how the remodelled atrial structure alters AF dynamics.…”
Section: Modelling the Heart Of Patientsmentioning
confidence: 99%